The influence of spiritual leadership on turnover intention: assessing mediating role of quality of work life and moderating role of organization climate - Neema Gasper Mariwa; Garba Betchem; Isaac Amankwaa Adu; Minkah Yaw Andrews (Yayasan Ahmar Cendekia Indonesia, 2021)
The purpose of this study is to investigate the influence of spiritual leadership on employees’ turnover intention by assessing the role of quality of work life as a mediating role and organizational climate as a moderator. This study identifies and examines, using a cross-sectional survey research design, the empirical support for two alternative model – a direct effect model and an indirect effect model of the likely effect of spiritual leadership on employee turnover intention, mediated by quality of work life and organizational climate as moderator on hotel employees of Tanzania. The results of this study showed the inverse relationship of spiritual leadership and turnover intention mediated by quality of work life. In addition organizational climate moderated the effect of quality of work life on turnover intention such that the relationship was stronger when organizational climate was high. The findings from this work adds to the existing literature and provide hotel managers with knowledge on the effects of spiritual leadership on turnover intention of employees. This is an original practical examination and its significance partly comes from its research implications and practice implications.